Characterisation of thermal annealed WOx on p-type silicon for hole-selective contacts. (21st July 2017) - Lee, Chang-Yeh; Aziz, Mohammad Izzat Abdul; Wenham, Stuart; Hoex, Bram
Abstract: Carrier-selective contacts have recently gained significant interest in the photovoltaic community. Apart from their minority and majority carrier properties, their thermal stability is also important from an application viewpoint. In this paper, we present a detailed study of the thermal stability of WO x, which is a promising hole-selective contact for silicon wafer solar cells. The film properties are studied after a post deposition annealing in the 200 to 800 °C temperature range. Fourier infrared transmission and X-ray diffraction measurements indicate that WO x films remain amorphous for annealing temperatures below 300 °C. For higher annealing temperatures, the film crystallises and a reduction in oxygen content is observed after 800 °C post deposition annealing. The resistance of the test structure Al/Si(p)/WO x /Al decreases rapidly at 600 °C. A minimum resistance of ∼32 mΩ·cm 2 was achieved after annealing at 700 °C. Photoluminescence imaging indicates that the minority carrier recombination significantly increases for annealing temperatures above 600 °C.